2021
DOI: 10.1158/1538-7445.sabcs20-pd13-09
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD13-09: Impact of neratinib on outcomes in HER2-positive metastatic breast cancer patients with central nervous system disease at baseline: Findings from the phase 3 NALA trial

Abstract: Background: The development of central nervous system (CNS) metastases presents a considerable challenge in metastatic breast cancer (MBC) due to the limited availability of evidence-based treatments. Up to 50% of patients with HER2-positive (HER2+) MBC develop CNS metastases during the course of their disease. Neratinib, an irreversible pan-HER tyrosine kinase inhibitor, has demonstrated activity against CNS metastases in HER2+ MBC in two phase 2 studies (NEfERT-T, TBCRC 022) and one phase 3 study (NALA); sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…20 The Panel is also aware of a San Antonio Breast Cancer 2020 presentation on the neratinib plus capecitabine versus lapatinib plus capecitabine regimen; however, abstracts are excluded as evidence. 10 The evidence is insufficient to make a recommendation in second-line and the Expert Panel will await a full publication and publications on other studies of this regimen.In addition to compounds previously discussed, a subgroup of patients receiving trastuzumab deruxtecan who have stable metastases, in the DESTINY 0-1 study, showed sustained response of 18.1 versus 16.4 months, regardless of CNS metastases. Because investigators presented this in an ASCO abstract that is not yet published, additional study is warranted.…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 The Panel is also aware of a San Antonio Breast Cancer 2020 presentation on the neratinib plus capecitabine versus lapatinib plus capecitabine regimen; however, abstracts are excluded as evidence. 10 The evidence is insufficient to make a recommendation in second-line and the Expert Panel will await a full publication and publications on other studies of this regimen.In addition to compounds previously discussed, a subgroup of patients receiving trastuzumab deruxtecan who have stable metastases, in the DESTINY 0-1 study, showed sustained response of 18.1 versus 16.4 months, regardless of CNS metastases. Because investigators presented this in an ASCO abstract that is not yet published, additional study is warranted.…”
Section: Recommendationsmentioning
confidence: 99%
“…The Panel is also aware of a San Antonio Breast Cancer 2020 presentation on the neratinib plus capecitabine versus lapatinib plus capecitabine regimen; however, abstracts are excluded as evidence. 10 The evidence is insufficient to make a recommendation in second-line and the Expert Panel will await a full publication and publications on other studies of this regimen.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, limited evidence of potential central nervous system activity of targeted agents, including alpelisib and olaparib, is available from case reports [17,18]. Additionally, in the NALA trial, neratinib in combination with capecitabine showed good efficacy in patients with HER2-positive BCBM [19]. Studies have previously examined the genomic landscape of BCBM and reported genomically distinct features from primary breast cancer as well as extracranial metastasis [20].…”
Section: Introductionmentioning
confidence: 99%